Hepatoprotective effect of red ginger rhizome extract in deep frying oil-fed male wistar rats - Sunarti Sunarti; Edy Fachrial; Urip Harahap; Delyuzar Delyuzar; Tri Widyawati; Lokot Donna Lubis (Universa Medicina, 2017)
BACKGROUNDNon-alcoholic steatohepatitis (NASH) is a chronic liver disease associated with increased free fatty acids, trans fatty acids and free radical compounds due to the consumption of deep frying oil (DFO). Ginger has hypolipidemic and antioxidant properties, and acts as an insulin sensitizer. The present study was conducted to evaluate the hepatoprotective effect of an ethanol extract of Zingiber officinale Roxb var rubrum (EEZO) in DFO-fed male Wistar rats.METHODSA study of experimental design was conducted involving 24 non-alcoholic steatohepatitis (NASH) male Wistar rats that were randomly divided into 4 groups. Group K1 (control) was given DFO-3 (3 times heated DFO) at a dose of 10 ìl/g BW/day. The treatment groups (P1, P2, P3) were given DFO-3 and red ginger rhizome extract at doses of 100, 200, and 400 mg/kg BW orally for 30 days. The histopathology examination assessed fatty degeneration, and degree of fibrosis. The data were analyzed with the Kruskal-Wallis and Mann-whitney test.RESULTS    The Kruskal-Wallis test showed that fatty degeneration (steatosis, lobular inflammation, hepatocyte ballooning and NASH) were significantly different among the four groups (p<0.05). Mann-Whitney test proved that fatty degeneration was not significantly different between control and treatment groups (p>0.05).CONCLUSIONDeep frying oil increased fatty degeneration and NASH, and none of red ginger rhizome extract doses was able to inhibit fatty degeneration significantly. For the future research it is intended to prolong the induction time and the administration of red ginger rhizome extract.